Blended and guided discovery learning strategy correlates with students’ academic performance in Unity Secondary Schools, South East, Nigeria - Ogedi Peter OKOLI; John Chukwuemeka Okoli (Jurnal Saintifik (Multi Science Journal), 2026)
Blended and guided discovery learning directs students towards discovery of new skills, knowledge and concepts. This learning process encourages students to think and analyse independently, so that they can identify concepts based on the material or data that has been provided. This makes diversity in teaching and learning approaches contribute to improved comprehension and retention of information. The purpose of this study is to determine the extent of the relationship between blended and guided discovery learning strategies and students’ academic performance in public secondary schools in South East, Nigeria. Quantitative research approach was used with a focus on correlational design. A population of 934 senior secondary two students in South East, Nigeria. A sample size of 280 senior secondary school students. Blended and Guided Discovery Learning Strategies Questionnaire (BGDLSQ) and Students Academic Performance Questionnaire (SAPQ) were used for data collection. Data collected from the field were analysed using the Pearson Product-Moment Correlation Coefficient to answer the research questions, while regression (ANOVA) was used to test the formulated null hypotheses at a 0.05 level of significance. The study concluded that the blended learning strategy significantly relates to a very great extent to students’ academic performance in Unity Secondary Schools in Southeast Nigeria. The coefficient of determination of 0.781 indicates that 78.1% of the variance observed in the students’ academic performance in Unity secondary schools in Southeast could be attributed to the blended learning strategy. When adopted in secondary schools, a blended learning strategy is likely to enhance students’ academic performance.